HRM/TQM Impact On Employees' Attitudes - Hussin, Huzaine (2010)
This research develops and investigative study the impact of HRM/TQM practices on employees' attitudes, namely job involvement, organizational commitment, job satisfaction, role ambiguity, and role conflict. The study samples are organizations in the Penang state of MalaysiaKajian in membuat penyelidikkan tentang impak amalan HRM/TQM atas sikap pekerja iaitu penglibatan kerja, komitment organisasi, kepuasan keija, ketaksaan tugas, dan percanggahan tugas.Sample kaji-selidik ini adalah organisasiorganisasi di negeri Penang, Malaysia